“LI KA FE’L TOU”: THE INFLUENCE OF AN EDUCATIONAL TELEVISION PROGRAM ON HAITIAN CHILDREN’S GENDER BELIEFS - Borzekowski, Dina L. G.; Mondestin, Tanesha; St-Onge Ahmad, Sacha (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
This study examined whether an educational television show would affect young Haitian children’s gender perceptions. We first collected data on children’s beliefs about male and female characteristics and roles. Among 862 participating 6- and 7-year-olds from urban, peri-urban, and rural settings, we saw gender stereotypical beliefs about activities, traits, and occupations. We conducted a school-based intervention over a 10-week period, in which children were randomly assigned to watch a children’s television program in either of two groups: one that watched Lakou Kajou or one that watched Dora the Explorer. Each group saw 21 episodes of its assigned show, spread over 3 screenings of 7 episodes each. Lakou Kajou is an educational television show created in Haiti that purposely incorporates overt counter-stereotypical gender messaging. Among those children who watched Lakou Kajou and recalled more characters from the show, beliefs around gender became less stereotypical. In countries like Haiti, where pronounced gender disparities and biases exist, it is encouraging to see that a locally produced educational television show can change beliefs.